2016
DOI: 10.1088/1748-9326/11/6/064003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil moisture deficits on Australian heatwaves

Abstract: Several regions of Australia are projected to experience an increase in the frequency, intensity and duration of heatwaves (HWs) under future climate change. The large-scale dynamics of HWs are well understood, however, the influence of soil moisture deficits-due for example to drought-remains largely unexplored in the region. Using the standardised precipitation evapotranspiration index, we show that the statistical responses of HW intensity and frequency to soil moisture deficits at the peak of the summer se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 30 publications
7
77
0
Order By: Relevance
“…(Kala, Evans & Pitman, ) focused on a single event and examined the sensitivity to soil moisture conditions 15 days prior to that event. In contrast, Herold et al () used a 3‐month timescale when examining the potential role of antecedent soil moisture conditions on heatwaves. Finally, Perkins et al () found that at longer timescales (~5 months) climate variability tends to have a larger impact on the background climate than soil moisture conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(Kala, Evans & Pitman, ) focused on a single event and examined the sensitivity to soil moisture conditions 15 days prior to that event. In contrast, Herold et al () used a 3‐month timescale when examining the potential role of antecedent soil moisture conditions on heatwaves. Finally, Perkins et al () found that at longer timescales (~5 months) climate variability tends to have a larger impact on the background climate than soil moisture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Land surface conditions can amplify surface temperatures, particularly during heatwave events (Fischer, Seneviratne, Lüthi, & Schär, ; Fischer, Seneviratne, Vidale, et al, ; Gibson et al, ; Hauser et al, ; Herold et al, ; Lorenz et al, ; Miralles et al, ). Globally, this influence has been attributed to precipitation deficits enhancing negative soil moisture anomalies, facilitating further surface warming by partitioning more energy into sensible heating (Mueller & Seneviratne, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other considerations include the land‐atmosphere coupling strength in climate models during simulated heat wave events [e.g., Miralles et al ., ]. The understanding of land atmosphere coupling on Australian heat waves remains limited compared to other regions, despite preliminary evidence for a significant soil moisture influence on heat waves for many parts of Australia [ Perkins‐Kirkpatrick et al ., ; Herold et al ., ]. As such, the ability for models to realistically capture these interactions will be important.…”
Section: Discussionmentioning
confidence: 99%